Measuring Rural Welfare in Colonial Uganda: Why Farmers Would not Work for Wages - Michiel de Haas (African Economic History Network (AEHN), 2014)
The majority of Africans in the colonial era pursued composite livelihood strategies of which commercial and subsistence agriculture were crucial components. So far, however, evidence on the contribution of these sources of non-wage income in African long-term welfare development is understudied. This paper presents a new approach to measure smallholder incomes in a temporal perspective. It introduces the concept of 'model farms' and exploits price series to arrive at 'smallholder welfare ratios'. The paper applies this approach to the cash crop regions of Uganda (1915-1970). The key finding of the paper is that during the colonial era ordinary rural dwellers in these regions of Uganda were slightly better off than previous estimates based on urban wages have suggested, but that living standards on individual smallholdings remained close to subsistence and did not develop much over time. The paper provides qualitative evidence to show how labour migration can explain low wage rates in the context of a thriving colonial cash crop economy. It also shows that in the late colonial and early post-colonial period, while real wages took off from the subsistence floor, the majority of smallholders began to fall behind.
Keywords: N37; N57; N97; 330; Living standards; welfare development; Uganda; agriculture; rural livelihoods